Alantolactone Induces Apoptosis in HepG2 Cells through GSH Depletion, Inhibition of STAT3 Activation, and Mitochondrial Dysfunction. (27th December 2012) - Khan, Muhammad; Li, Ting; Ahmad Khan, Muhammad Khalil; Rasul, Azhar; Nawaz, Faisal; Sun, Meiyan; Zheng, Yongchen; Ma, Tonghui
Abstract : Signal transducer and activator of transcription 3 (STAT3) constitutively expresses in human liver cancer cells and has been implicated in apoptosis resistance and tumorigenesis. Alantolactone, a sesquiterpene lactone, has been shown to possess anticancer activities in various cancer cell lines. In our previous report, we showed that alantolactone induced apoptosis in U87 glioblastoma cells via GSH depletion and ROS generation. However, the molecular mechanism of GSH depletion remained unexplored. The present study was conducted to envisage the molecular mechanism of alantolactone-induced apoptosis in HepG2 cells by focusing on the molecular mechanism of GSH depletion and its effect on STAT3 activation. We found that alantolactone induced apoptosis in HepG2 cells in a dose-dependent manner. This alantolactone-induced apoptosis was found to be associated with GSH depletion, inhibition of STAT3 activation, ROS generation, mitochondrial transmembrane potential dissipation, and increased Bax/Bcl-2 ratio and caspase-3 activation. This alantolactone-induced apoptosis and GSH depletion were effectively inhibited or abrogated by a thiol antioxidant, N-acetyl-L-cysteine (NAC). The data demonstrate clearly that intracellular GSH plays a central role in alantolactone-induced apoptosis in HepG2 cells. Thus, alantolactone may become a lead chemotherapeutic candidate for the treatment of liver cancer.